PENGARUH SISTEM PENGENDALIAN INTERNAL, SUMBER DAYA MANUSIA BIDANG AKUNTANSI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KETERANDALAN LAPORAN KEUANGAN SKPD (Studi Persepsian SKPD Se Kabupaten Agam) - Seprizal -; Ria Nelly Sari; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to examine the effect of internal control system, human resources on accounting division, information technology utilization to reliability of financial statements. This research was opinion research, population of this research was SKPD’s accounting staff. Sampling method used was puposive sampling method. Statistical method to test the hypothesis was multiply regression using software SPSS 20. The result of this research showed internal control system and human resources on accounting division effects the reliability of financial statements but the information technology utilization was not effect the reliability of financial statements. The magnitude (R2) of internal control system, human resources on accounting division, and information technology to reliability of financial statements was 46,4 % and the remaining 53,6% effected by other variable.Keywords: internal control, human resources, information technology, and financial statements